Relative Importance Measurement of the Moral Intensity Dimensions - Tsalikis, John (Journal of business ethics, 2008)
The relative importance of the Jones’ [Jones, T. M.: 1991, Academy of Management Review 16(2), 366–395] six components of moral intensity was measured using a conjoint experimental design. The most important components influencing ethical perceptions were: probability of effect, magnitude of consequences, and temporal immediacy. Contrary to previous research, overall social consensus was not an important factor. However, consumers exhibit distinctly different patterns in ethical evaluation, and for approximately 15% of respondents social consensus was the most important dimension.